Pedestrians’ experience in urban street environments exploring barrier effects of central streets in Gothenburg City - Lindfors Ljuhs, Annie; Lysö, Frida (My University, 2024)
While barrier effects are commonly studied on large infrastructure elements through street network analysis, perceptions of barrier effects occurring from central city streets are rarely explored. Therefore, this master’s thesis adopts a methodology based on a case study, where three central, busy streets in Gothenburg city are under examination to understand the perception of barrier effects occurring from these city streets. Since volume of motorised traffic is a commonly used factor indicating barrier effects the case streets were primarily selected based on high and similar traffic flows. Furthermore, the underlying premise of this study is that if the experience of barrier effects differs between the streets, additional factors, other than traffic flow, may influence the perception of these barriers. The experiences of a selection of barrier effects and various attributes in the streetscape categorised as ’Transport features and crossing facilities’ and ’Environmental features’, were collected through a survey. The survey was administrated through a survey tool integrated with GIS, known as Public Participatory Geographic Information System (PPGIS), which facilitated data collection of geographic and non-geographic information. Associations between the barrier effects and attributes were examined mainly through binomial regression analyses to understand what features influence the perception of barrier effects. In addition, qualitative data such as spatial data and free-text answers were collected. For this data, methods of thematic analysis and spatial analysis were employed to enhance the depth of the study. Additionally, the impact of age and gender were analysed. The main outcome of this thesis is that barrier effects are experienced on central city streets. The results also indicate that vehicular speed, the distance between crossing facilities, the presence of obstacles, and pavement width are key factors influencing the perception of barrier effects. Regarding the impact of demographics, no conclusions could be drawn regarding age. Additionally, the regression analysis models did not show a significant difference between genders, contradicting previous assumptions in the literature about gender differences.
Keywords: barrier effects, pedestrian experience, city streets, perception, transport infrastructure, walking environment, impact of streetscape features, binomial logistic regression analysis, PPGIS